# Find (f+g) and (f-g)(x) for f(x)=10x^2+8 and g(x)=2-5x

Alright class, let's take a look at the required solutions which are (f+g)(x) = 10x² + 10 - 5x and (f-g)(x) = 10x² + 6 + 5x. Now, what exactly is a function? Well, it's a mathematical expression that describes the relationship between two variables. In this case, we have been given the functions f(x) = 10x² + 8 and g(x) = 2 - 5x. To calculate (f+g)(x), we simply add the two functions term by term which gives us (f+g)(x) = f(x) + g(x). By substituting the given function values in the equation, we get (f+g)(x) = 10x² + 8 + (2 - 5x), which simplifies to (f+g)(x) = 10x² + 10 - 5x. To find (f-g)(x), we subtract g(x) from f(x) term by term which gives us (f-g)(x) = f(x) - g(x). By substituting the given function values in the equation, we get (f-g)(x) = 10x² + 8 - (2 - 5x), which simplifies to (f-g)(x) = 10x² + 6 + 5x. To learn more about functions, you can refer to the link provided in the question which is brainly.com/question/12431044. #SPJ1